Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

An examination of the trade in bear parts and derivatives for traditional medicine in Hong Kong and its legality - Lalita Gomez; Jovy Y. S. Chan; Leni H. T. Cheung; Sze-Wing Chan; Chris R. Shepherd (European Journal of Wildlife Research, 2024)

Corrigendum to “Hong Kong's subtropical scleractinian coral communities: Baseline, environmental drivers and management implications” [Mar. Pollut. Bull. 167 (2021): 112289] - Yip Hung Yeung; James Y. Xie; Chun Kit Kwok; Keith Kei; Put Ang; Leo Lai Chan; Walter Dellisanti; Chi Chiu Cheang; Wing-kuen Chow; Jian-Wen Qiu (Marine Pollution Bulletin, 2023)

Patient attitudes towards brain donation across both neurodegenerative and non-neurodegenerative neurological disorders - Reudi J. W. Chan; Sherilyn Seah; Joel Y. J. Foo; Alisa C. W. Yong; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Louis C. S. Tan; Adeline S. L. Ng (Cell and Tissue Banking, 2020)

Attitudes of Asian Parkinson patients towards brain donation - Shazma Khan; Joel Y. J. Foo; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Adeline S. L. Ng; Louis C. S. Tan (Cell and Tissue Banking, 2019)

Shifting paradigms in restoration of the world's coral reefs - Madeleine J. H. van Oppen; Ruth D. Gates; Linda L. Blackall; Neal Cantin; Leela J. Chakravarti; Wing Y. Chan; Craig Cormick; Angela Crean; Katarina Damjanovic; Hannah Epstein; Peter L. Harrison; Thomas A. Jones; et al. (Global Change Biology, 2017)
Many ecosystems around the world are rapidly deteriorating due to both local and global pressures, and perhaps none so precipitously as coral reefs. Management of coral reefs through maintenance (e.g., marine‐protected areas, catchment management to improve water quality), restoration, as well as global and national governmental agreements to reduce greenhouse gas emissions (e.g., the 2015 Paris Agreement) is critical for the persistence of coral reefs. Despite these initiatives, the health and abundance of corals reefs are rapidly declining and other solutions will soon be required. We have recently discussed options for using assisted evolution (i.e., selective breeding, assisted gene flow, conditioning or epigenetic programming, and the manipulation of the coral microbiome) as a means to enhance environmental stress tolerance of corals and the success of coral reef restoration efforts. The 2014–2016 global coral bleaching event has sharpened the focus on such interventionist approaches. We highlight the necessity for consideration of alternative (e.g., hybrid) ecosystem states, discuss traits of resilient corals and coral reef ecosystems, and propose a decision tree for incorporating assisted evolution into restoration initiatives to enhance climate resilience of coral reefs.

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

Expression and Localization of PRiMA-Linked Globular Form Acetylcholinesterase in Vertebrate Neuromuscular Junctions - Karl W. K. Tsim; K. Wing Leung; Ka Wai Mok; Vicky P. Chen; Kevin Y. Zhu; Judy T. T. Zhu; Ava J. Y. Guo; Cathy W. C. Bi; Ken Y. Z. Zheng; David T. W. Lau; Heidi Q. Xie; Roy C. Y. Choi (Journal of Molecular Neuroscience, 2010)

Analysis of FTO gene variants with measures of obesity and glucose homeostasis in the IRAS Family Study - Maria R. Wing; Julie Ziegler; Carl D. Langefeld; Maggie C. Y. Ng; Steven M. Haffner; Jill M. Norris; Mark O. Goodarzi; Donald W. Bowden (Human Genetics, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The pharmacokinetics of erythropoietin in the cerebrospinal fluid after intravenous administration of recombinant human erythropoietin - Anargyros Xenocostas; Wing K. Cheung; Francis Farrell; Cindy Zakszewski; Marian Kelley; Andrzej Lutynski; Michael Crump; Jeffrey H. Lipton; Thomas L. Kiss; Catherine Y. Lau; Hans A. Messner (European Journal of Clinical Pharmacology, 2005)

A bacterial artificial chromosome library for barley (Hordeum vulgare L.) and the identification of clones containing putative resistance genes - Y. Yu; J. P. Tomkins; R. Waugh; D. A. Frisch; D. Kudrna; A. Kleinhofs; R. S. Brueggeman; G. J. Muehlbauer; R. P. Wise; R. A. Wing (Theoretical and Applied Genetics, 2000)

A bacterial artificial chromosome library for sugarcane - J. P. Tomkins; Y. Yu; H. Miller-Smith; D. A. Frisch; S. S. Woo; R. A. Wing (Theoretical and Applied Genetics, 1999)

Optimal placement of impedance epigastrography electrodes - Wing C. Kee; Y. Jack Kingma; Martin P. Mintchev; Kenneth L. Bowes (Annals of Biomedical Engineering, 1996)